Comparative nutritional indicators as markers for resilience: the impacts of low-intensity violence among three pastoralist communities of northern Kenya. Issue 1 (2nd January 2016) - Pike, Ivy L.; Straight, Bilinda; Hilton, Charles; Österle, Matthias
ABSTRACT: We present results from a collaborative project on the consequences of endemic violence in the pastoralist zone of Northern Kenya. Drawing on our ethnographically driven epidemiological approach, we examine the differential cost of violence by examining household nutrition. The case/control approach we employ draws data from six sites that are culturally similar but differ in the degree of exposure to, or relative insulation from, violence. As one of many lenses through which to examine the consequences of endemic violence, nutritional status offers a different story than assessing livestock holdings or access to land. Our data suggest that despite the different strategies that the pastoralist communities employ to contend with the violence, each one comes with nutritional consequences. Measuring the direct and indirect effects of violence in communities already compromised by poverty and episodic drought challenges researchers, policy-makers, and humanitarian organizations. Our goal is to offer insights into reasonable pathways for understanding these intersections of insecurity for policy and humanitarian organizations.